Is the evaluation of "traditional" physicochemical parameters sufficient to explain the potential toxicity of the treated wastewater at sewage treatment plants? - Vasquez Christodoulou, Marlen; Fatta-Kassinos, Despo (My University, 2013)
Water scarcity is one of the most important environmental and public health problems of our century. Treated wastewater reuse seems to be the most attractive option for the enhancement of water resources. However, the lack of uniform guidelines at European and/or Mediterranean level leaves room for application of varying guidelines and regulations, usually not based on risk assessment towards humans and the environment. The benefits of complementing the physicochemical evaluation of wastewater with a biological one are demonstrated in the present study using Cyprus, a country with extended water reuse applications, as an example. Four organisms from different trophic levels were used for the biological assessment of the wastewater, namely, Pseudokirchneriella subcapitata, Daphnia magna, Artemia salina and Vibrio fischeri. The physicochemical assessment of wastewater based on "traditional" chemical parameters indicated that the quality of the wastewater complies with the limits set by the relevant national guidelines for disposal. The ecotoxicological assessment, however, indicated the presence of toxicity throughout the sampling periods and most importantly an increase of the toxicity of the treated wastewater during summer compared to winter. The resulting poor correlation between the physicochemical and biological assessments demonstrates that the two assessments are necessary and should be performed in parallel in order to be able to obtain concrete results on the overall quality of the treated effluent. Moreover, a hazard classification scheme for wastewater is proposed, which can enable the comparison of the data sets of the various parameters deriving from the biological assessment in a comprehensive way.
Keywords: Whole effluent toxicity; WET; Cluster analysis; Ecotoxicity of wastewater; Hazard classification